Palm Leaf Processing as Ruminant Feeds - Suyitman; Warly, Lili; Evitayani (Pakistan Journal of Nutrition, 2013)
This study aims to determine the best processing methods of palm leaves that can improve nutrient and digestibility as ruminant feed. An in vitro study was conducted from June, 15th 2012 until September, 20nd 2012. Palm leaf samples were analyzed using Proximate and Van Soest method in Laboratory of Ruminant Nutrition of the Faculty of Animal Husbandry, University Andalas, Padang. This study is an experimental study that uses a completely randomized design with 5 (five) treatment and 4 (four) replications. Treatment consists of: A = control (no treatment), B = physical processing (steam), C = chemical processing (ammoniation), D = biological treatment (ensilage) and E = combination of physical-chemical properties (steam-ammoniation). Data were analyzed using analysis of variance (ANOVA). Differences between treatments were tested by Duncan’s Multiple Range Test (DMRT). The results showed that treatment of C = chemical processing palm leaf (ammoniation) provides nutrients and better digestibility than some other palm leaf processing methods with its nutritional value was as follow: dry matter (41.51%), organic matter (86.56%), crude protein (14.65%), NDF (53.22%), ADF (40.76%), cellulose (19.67%), hemicellulose (12.46%), lignin (9, 91%). In vitro digestibility were as follow: dry matter (36.57%), organic matter (43.88%), crude protein (47.24%), NDF (32.65%), ADF (23.70%), cellulose (30.30%), hemicellulose (51.94%). Rumen fluid characteristics: pH (7.10), VFA (135.55 mM) and NH3-N (58.72 mg/100 ml).